Respiratory muscle training extends exercise tolerance without concomitant change to peak oxygen uptake: Physiological, performance and perceptual responses derived from the same incremental exercise test. Issue 6 (25th July 2013) - Edwards, A. M.
Abstract: Background and objective: There is conjecture over the efficacy of respiratory muscle training (RMT). The aim of this study was to establish whether or not exercise tolerance, physical performance and effort perceptions are influenced by RMT. Methods: Thirty‐six healthy males (age 24 ± 4) agreed to participate (experimental group (EXP) n  = 18, control (CON) n  = 18). RMT was performed using an inspiratory pressure‐threshold training device at either 55% (EXP) or 10% (CON) of maximal inspiratory effort. Measurements of spirometry and maximal static inspiratory mouth pressure were taken before and after 4 weeks of RMT in addition to an incremental test to volitional exhaustion for the determination of: (i) V ˙ O 2 p ⁢ e a k ; (ii) maximal velocity at volitional exhaustion ( v V ˙ O 2 p ⁢ e a k )); (iii) time to volitional exhaustion; and (iv) effort perceptions. Results: There were no differences in spirometry, but mean maximal static inspiratory mouth pressure increased significantly in EXP ( P  < 0.01). V ˙ O 2 p ⁢ e a k was unchanged following the 4‐week intervention for both EXP and CON, although the proportion of EXP attaining the criteria for a V ˙ O 2 plateau significantly increased ( P  < 0.05). Both time to volitional exhaustion ( P  < 0.05) and v V ˙ O 2 p ⁢ e a k were significantly improved for EXP ( P  < 0.05), while effort perceptions were reduced ( P  < 0.05). Conclusions: EXP tolerated higher running velocities during incremental exercise and demonstrated a significant flattening (plateau) of V ˙ O 2 after training. This suggests that RMT may promote an improved performance outcome v V ˙ O 2 p ⁢ e a k probably as a result of blunted afferent sensations reducing the perceived discomfort of exercise at high ventilatory loads. Abstract : Following RMT, the performance variables peak running velocity and time to volitional exhaustion are both improved in response to the same incremental exercise test while peak oxygen uptake is unaffected. This observation supports the contention that exercise tolerance is improved following RMT.